Particle networks from powder mixtures: Generation of TiO2-SnO2 heterojunctions via surface charge-induced heteroaggregation - Siedl, Nicolas; Baumann, Stefan O.; Elser, Michael J.; Diwald, Oliver (Journal of Physical Chemistry C, 2012)
We explored the impact of interfacial property changes on aggregation behavior and photoinduced charge separation in mixed metal oxide nanoparticle ensembles. TiO2 and SnO2 nanoparticles were synthesized by metal organic chemical vapor synthesis and subsequently transformed into aqueous colloidal dispersions using formic acid for adjustment of the particles’ surface charge. Surface charge-induced heteroaggregation was found to yield blended nanoparticle systems of exceptionally high mixing quality and, after vacuum annealing, to extremely high concentrations of heterojunctions between TiO2 and SnO2 nanoparticles with dehydroxylated surfaces. For tracking charge transfer processes across heterojunctions, the photogeneration of trapped charge carriers was measured with electron paramagnetic resonance (EPR) spectroscopy. On blended nanoparticles systems with high concentrations of SnO2–TiO2 heterojunctions, we observed an enhanced cross section for interparticular charge separation. This results from an effective interfacial charge transfer across the interfaces and gives rise to substantially increased concentrations of electrons and hole centers. The here presented insights are key to the rational design of particle-based heterojunctions and mesoporous nanoparticle networks and help to engineer composite nanomaterials for photocatalysis and solar energy conversio